The Role of Value-Based Leadership in Shaping an Organizational Culture that Supports Sustainable Change - Purnomo, Yudiyanto Joko; Siminto; Ausat, Abu Muna Almaududi (ADMAN: Journal of Contemporary Administration and Management, 2024)
In an ever-changing business environment, organizations must be able to adapt to remain relevant. Change is no longer a one-time occurrence but a constant that needs to be managed effectively. This research aims to analyze the role of value-based leadership in shaping an organizational culture that supports sustainable change. The research method employed is a literature review with a qualitative approach using descriptive analysis. Data for this research were gathered from Google Scholar within the timeframe of 2004-2024. The findings indicate that leaders with a value-based approach play a crucial role in shaping an organizational culture that supports sustainable change. They are responsible for communicating and reinforcing core values, developing a focused vision, building trust and team member engagement, as well as promoting continuous learning. Additionally, they must be adept at managing conflicts, considering sustainability aspects in resource management, and confronting uncertainty with flexibility and adaptability. Value-based leaders also need to ensure that proposed changes align with the interests of all organizational stakeholders.